Transformational Leadership and Work Motivation in Enhancing Innovative Work Behavior: The Mediating Role of Job Satisfaction in Hospitality Sector Employees - Afriandika, Ivan Riski; Bagis, Fatmah; Endratno, Hermin; Rahmawati, Ika Yustina (Asian Journal of Management Analytics, 2025)
Behavior innovative work​ Still become necessary factors​ be considered and improved, especially in the sector services in Banyumas, Indonesia. Research This aims to​​ to study influence leadership transformational and motivational Work to behavior innovative work, with​ satisfaction Work as variable mediation. Questionnaire given online using Google Form, and is carried out with use approach quantitative with technique taking sample using accidental sampling. Population in study This as many as 255 and the samples used is 162 respondents from employees in the sector hospitality in Banyumas. Research This using SEM-PLS for analyze data. Research results show that, although motivation work and leadership transformational No in a way direct influence behavior innovative, both in a way significant influence satisfaction work, which is positive arrange connection between both and behavior innovative in place Work.